Problematik Pendidikan Bahasa Indonesia Kajian Pembelajaran Bahasa Indonesia pada Sekolah Dasar - Muhammad Zuhdy Hamzah; Muhamad Alfi Khoiruman (Jurnal Syntax Transformation, 2021)
Learning is a permanent change in student behavior through experience, observation, and language, which is actively related to knowledge, attitudes and skills. This study aims to describe the problems of Indonesian language education, especially the study of how students learn the language in learning Indonesian. The approach used in this research is descriptive qualitative. Primary data was obtained through an interview study of teachers and students' guardians. Observations were made to see students' problems in learning Indonesian. The results of the study indicate that in language learning in schools, especially elementary schools, teachers evaluate and understand that students before entering school have learned language (language acquisition) through their living environment. Students will be more confident in learning a language if students are given the opportunity to improve their own work. Language learning provides opportunities for students to choose language activities. Furthermore, educators are more careful and selective in their role as professional educators (understanding aspects of language knowledge, level of language knowledge, and the important role of language skills. For other researchers, the results of this study can provide benchmarks for answers to problems in accordance with the formulation problems; as a motivation for other researchers to be more active in contributing the results of scientific work in the development of language